EFFECT OF WHOLE BODY VIBRATION ON LOWER BODY STRENGTH AND BALANCE IN OSTEOARTHRITIS KNEE (International Journal of Physiotherapy, 2020)
Background: Knee osteoarthritis causes pain, functional limitation, and disability in the elderly. Whole-body vibration has gained a lot of attention in recent years. It is currently used in alleviating pain and improve physical function along with strength and balance.Methods: 34 individuals aged between 50-70 years fulfilling the inclusion criteria were selected and randomized into two groups. Baseline assessment was done using the VAS scale, WOMAC scale, Berg Balance Scale, and 30seconds chair stand test. Group A received whole-body vibration, and knee strengthening exercises, and group B received only strengthening exercises. The treatment was given thrice in a week for four weeks. The assessment was done by the end of the 2nd and 4th weeks.Results: Whole body vibration had shown greater improvement of VAS on rest (p